The Benefit of Family Nursing Care in Improve Knowledge and Prevent the Deformity of Leprosy Patient - Nursalam Nursalam; Makhfudli Makhfudli; Indra Alamsyah (Jurnal Ners, 2009)
Introduction : Leprosy is one of contagious illness which generates complex situation. The main problem of this study was faced by family in taking care of leprosy. Purpose of this research was to analyze the effect of applied family nursing care to knowledge and prevent dissability patient of leprosy.Method : Design used in this reseach was pre experiment. The population of this study was all family and patient of leprosy in Puskesmas Taliwang-Nusa Tenggara Barat,  whom deal directly with the client. Data were analyzed using wilcoxon signed rank test and fisher exact probability test with level of significance α ≤ 0,05.Result : Results showed that applied family nursing care is an early preventing and continued care is one of the methods to increase family knowledge and  prevent the dissability of leprosy reaction to the patient.Conclusion : It is recomended that the  involvement of the family in caring is important.